Komparasi Berita Negatif dan Positif Mengenai Covid-19 Di Situs Detik dan Kompas - Cintia Caroline (President University, 2020)
The paradigm of bad news is good news in journalism reflects that the public is more interested in negative news. Valuable news usually contains conflicts that important for people. Currently, the global health crisis issue caused by Covid-19 virus is being highlighted by media around the world, it is causing chaos because no country is ready to face this problem. Unbalanced news was presented by media in Indonesia and caused public panic, especially by the online media that could indirectly affect the spread of Covid-19. Two popular news sites in Indonesia, Detik and Kompas, provide both bad and good news regarding the Covid-19 pandemic. To find out the comparison of the news presentation from these two sites, this study uses quantitative analysis methods. The results show that Kompas are quite balanced, while Detik tends to present bad news which can indirectly worsen the spreading of Covid-19 in Indonesia.